Method for producing high-purity silicon through precise gradient cooling centrifugation by comprehensively utilizing aluminum-silicon raw materials
The low-grade silicon-aluminum raw materials are processed through precise gradient cooling centrifugation method to form a skeleton structure of silicon-aluminum-ferroalloy, and high-purity single silicon is obtained through separation and reselection, which solves the problem of low-grade raw materials utilization and achieves efficient resource utilization and environment Protect.
Patent Information
- Application Number
- CN202310976710.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively use low-grade silicon-aluminum raw materials to produce high-purity silicon, resulting in waste of resources and environmental pollution.
Accurate gradient cooling centrifugation method is used to crush and mix silicon-aluminum raw materials with carbonaceous reducing agent, and obtain aluminum-ferrosilicon melt through arc furnace reduction reaction, followed by gradient cooling and centrifugation to form silicon-aluminum-ferrosilicon alloy with a skeleton structure. , and the high purity elemental silicon was obtained through multiple crushing, screening and reselection separation.
It has achieved efficient utilization of low-grade silicon aluminum raw materials, produced high-purity silicon products, solved the problems of resource waste and environmental pollution, and expanded the raw materials for industrial silicon and high-purity silicon.
Smart Images

Figure CN119430186A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of smelting technology, and in particular relates to a method for producing high-purity silicon by comprehensive utilization of aluminum-silicon raw materials through precise gradient cooling and centrifugation. Background Art
[0002] Industrial silicon, also known as quasi-metallic silicon, is mainly used for the production of organic silicon, the preparation of high-purity crystalline silicon materials, and the configuration of silicon-aluminum alloys. Therefore, it is widely used in the production of organic silicon products such as silicone oil, silicone rubber, silicone resin and silane coupling agent, as well as crystalline silicon products used in semiconductor industries such as solar cells and chips, and aluminum-silicon alloys used in the automotive manufacturing industry. The production of industrial silicon is currently produced by smelting silica and carbonaceous reducing agents in a submerged arc furnace, and then casting, cooling, crushing and other steps. Its upstream raw materials are relatively simple, the production process is fixed, and the purity of the raw materials is required to be high. Silica is the main raw material for the production of industrial silicon. Although my country is rich in silicon ore resources, with the rapid development of the industrial silicon industry and the need for environmental protection, the available resources are also sharply reduced. Therefore, in the face of the current situation where the demand for industrial silicon is growing with the rapid development of modern industry, science and technology, it is of great strategic significance and practical value to seek more universal production processes and broaden the source of raw materials.
[0003] Low-grade silicon-alumina raw materials are natural minerals, industrial waste residues, tailings, etc., with silicon oxide and aluminum oxide as the main components. There are many types in nature, abundant reserves, and low prices, such as low-grade bauxite, kaolinite, clay, kyanite, fly ash, coal gangue, etc. Due to the relatively low aluminum content and high silicon / aluminum ratio, they are not suitable for use as raw materials for the current conventional aluminum industry production, nor can they be used as raw materials for the current industrial silicon production. They can only be used to produce low-value-added products such as ecological bricks, or for landfill treatment, which not only pollutes the environment, but also causes a waste of resources.
[0004] In the prior art, Chinese patent applications CN202011267903.8 and CN202011267925.4 respectively provide a method for preparing aluminum-silicon-iron alloy using high-aluminum coal gangue and grading purification, and a method for preparing aluminum-silicon-iron alloy using high-aluminum fly ash and grading purification. These two methods can obtain aluminum-silicon alloy for casting, aluminum-silicon-iron alloy for deoxidizer, and industrial silicon through graded purification. However, the raw materials used in these two methods are both high in aluminum content, which limits their application.
[0005] In summary, if we can reasonably utilize the silicon and aluminum resources in low-grade silicon-aluminum raw materials and realize the production of high-purity silicon with low-grade silicon-aluminum resources, it will break through the current raw material limitations of silicon industrial production. Summary of the invention
[0006] The technical solution adopted by the present invention to solve the technical problem is:
[0007] A method for producing high-purity silicon by comprehensive utilization of aluminum silicon raw materials through precise gradient cooling and centrifugation, the steps are:
[0008] (1) crushing the silicon-aluminum raw material and the carbonaceous reducing agent, adding a binder and water to mix them evenly, forming agglomerates, drying to obtain dry agglomerates, and then putting them into an electric arc furnace for reduction reaction to obtain a single-element aluminum-ferrosilicon melt;
[0009] (2) Under controlled cooling conditions, the obtained aluminum-silicon-iron melt is subjected to gradient cooling, wherein the gradient cooling includes the following stages: in the first stage, the temperature is reduced to 800-1300° C. at a cooling rate of 1-20° C. / min and kept at this temperature for 10-200 min; in the second stage, the temperature is reduced to 650-1000° C. at a cooling rate of 0.1-20° C. / min and kept at this temperature for 10-200 min; in the third stage, the temperature is reduced to 600-850° C. at a cooling rate of 0.1-20° C. / min and kept at this temperature for 10-200 min; in the fourth stage, the temperature is reduced to 570-650° C. at a cooling rate of 0.1-20° C. / min to obtain a silicon-aluminum-iron alloy with a skeleton structure;
[0010] (3) the obtained silicon-aluminum-iron alloy with a skeleton structure is heated to 580-700° C. and centrifuged to achieve solid-liquid separation, wherein the solid state is maintained as an interwoven skeleton structure formed by the growth of silicon phase and iron phase;
[0011] (4) crushing and sieving the solid porous interwoven skeleton structure sample composed of silicon phase and iron phase skeleton obtained in the previous step to 40-200 mesh;
[0012] (5) The sieved sample obtained in the previous step is subjected to gravity separation to separate the silicon phase and the iron phase, and the low-density sample is collected as a high-silicon sample;
[0013] (6) The high-silicon sample obtained in the previous step is soaked in 1-5 mol / L hydrochloric acid for 24 hours to obtain elemental silicon with a purity higher than 99.9%, i.e., the high-purity silicon.
[0014] In the above method, the silicon-alumina raw material in step (1) can be selected from high-grade silicon-alumina raw materials, but in the method of the present invention, the silicon-alumina raw material can be selected from low-grade silicon-alumina raw materials, wherein Al 2 O 3 The content is not higher than 55%, and the Al / Si (mass ratio) is not higher than 3.
[0015] In the above method, the silicon-alumina raw material in step (1) can be one or a mixture of natural silicon-alumina minerals, solid waste containing silicon-alumina, or artificially synthesized silicon-alumina raw materials, wherein the natural silicon-alumina minerals include bauxite, kaolinite, albite, potassium feldspar, etc., and the solid waste containing silicon-alumina includes bauxite flotation tailings, coal gangue, fly ash, shale slag, etc.
[0016] In the above method, after the silicon-aluminum raw material and the carbonaceous reducing agent in step (1) are added together, the ratio of the three elements of aluminum, silicon and iron is as follows: the aluminum content is 10-88.3wt.%, the silicon content is 11.7-90wt.%, the iron content is 0.01-26.0wt.%, and the iron content is ≤(45.64-0.52Al)wt.% and ≤(40.63-0.41Si)wt.%.
[0017] In the above method, the carbonaceous reducing agent in step (1) includes coal, petroleum coke, calcined anthracite, coke, metallurgical coke, one of which or a mixture of several thereof.
[0018] In the above method, the amount of the carbonaceous reducing agent in step (1) is 90-95% of the required reducing agent. If it exceeds 95%, the metal carbides (especially aluminum carbide) in the alloy will increase, which will not only reduce the alloy yield but also affect the stability of arc furnace smelting.
[0019] In the above method, the mass of the binder added in step (1) is 5-10% of the mixed material, the pelletizing pressure is 50-150 MPa, the pellet drying temperature is 150-200°C, and the moisture content of the pellets after drying is not more than 1%.
[0020] In the above method, the reduction reaction temperature in the electric arc furnace in step (1) is 2200-2500°C.
[0021] In the above method, the interwoven skeleton structure described in step (2) is a skeleton structure constructed by silicon grains and iron phase grains, which still retains the macroscopic structure of the aluminum-silicon-iron alloy described in step (1) to a certain extent in appearance after centrifugal treatment, but is loose and porous inside; the gaps in the skeleton structure are filled with aluminum-silicon alloy similar to a binder.
[0022] In the above method, the silicon phase in the interwoven skeleton structure is mainly composed of silicon element.
[0023] In the above method, the Fe mass content of the iron phase in the interwoven skeleton structure is 9.7-65%, the Al mass content is 10-68%, and the Si mass content is 12-30%.
[0024] In the above method, the phase composition of the iron phase in the interwoven framework structure is Al 4FeSi、Al 3 FeSi 2 、Al 2 Fe 5 Si 5 、Al 9 Fe 5 Si 5 、Al 3 Fe 3 Si 2 One or several of them are mainly used.
[0025] In the above method, in step (3), the sample is centrifuged for 0 to 360 minutes, the supergravity coefficient is 50 to 500 g, and the separation time is 30 to 360 minutes.
[0026] In the above method, the crushing described in step (4) can be carried out by a hammer crusher, a jaw crusher, a disc crusher, a double-roll crusher, etc., and the mesh size requirement can be achieved through a cyclic crushing method.
[0027] In the above method, the crushing described in step (4) can first be crushed into small pieces with a particle size of 10-20 mm using a hammer crusher, jaw crusher, disc crusher, double-roll crusher, etc., and then the sample can be wet-crushed using a disc crusher, and then wet-sieved using a vibrating screen to obtain a 40-200 mesh sample.
[0028] In the above method, the high-silicon sample described in step (5) refers to a silicon-rich phase with an iron content of less than 0.5% obtained after the self-generated aluminum element in the system is removed by the reduction of the silicon-aluminum raw material.
[0029] In the above method, the re-selection described in step (5) can be separated by a shaking table. The sample after crushing in step (4) is adjusted to a solid-liquid ratio of 1:10 to 1:50, and the slurry is injected into the ore dressing shaking table at a flow rate of 10 to 30 ml / s. The inclination angle of the ore dressing shaking table is set to 5-10°, and the flushing water flow of the ore dressing shaking table is set to 20 to 100 ml / s. A dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase to collect silicon-rich phase samples. The collected high-silicon sample is then injected into the ore dressing shaking table again at a flow rate of 5 to 20 ml / s. The inclination angle of the ore dressing shaking table is set to 3 to 6°, and the flushing water flow of the ore dressing shaking table is set to 20 to 40 ml / s. At this time, the dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase, 5 to 15 mm away from the silicon phase. The high-silicon sample collected again has an iron content of less than 0.5%.
[0030] In the above method, the gravity separation described in step (5) can be carried out by using a cyclone chute to prepare a slurry of about 2-40% of the crushed sample in step (4). After separation, the collected samples with low density are polycrystalline silicon, and the samples with high density are iron-rich phase.
[0031] In the above method, the gravity separation described in step (5) can be separated by a two-product heavy medium cyclone. The solid-liquid ratio of the sample to the heavy medium suspension after screening is 1:2.5-1:4.5, the volume concentration of the heavy medium suspension is 15%-30%, and the heavy medium suspension is composed of one or more of sodium polytungstate, calcium bromide, zinc bromide or calcium iodide. After sorting, the collected low-density sample is polysilicon; the high-density sample is an iron-rich phase.
[0032] The cooling mechanism of the present invention is:
[0033] When the melt is cooled, solidification phases gradually precipitate from the material, and the following steps are performed:
[0034] L→Si
[0035] L→Si+Al 3 FeSi 2
[0036] L+Al 3 FeSi 2 →Al 4 FeSi+Si
[0037] L→Al+Si+Al 4 FeSi
[0038] First, in the primary crystallization area of silicon, when the melt begins to cool down, the elemental Si phase will precipitate first as the temperature continues to drop; then, after entering the iron-rich phase area, Al 3 FeSi 2 As the temperature continues to drop, there will be a melting process, that is, the phase melts with the remaining liquid phase to form Al 4 FeSi phase and elemental silicon; finally, when the temperature reaches the low eutectic temperature of the system, the liquid phase will completely solidify and precipitate into elemental aluminum, elemental silicon and Al 4 FeSi phase.
[0039] According to the ratio of aluminum, silicon and iron in the raw materials, the cooling and condensation process is different. In particular, when the melt cooling mechanism is precisely controlled, the grain size of each solidified phase can be effectively controlled, so that after full growth, a silicon phase and an iron-rich phase with larger grain size can be obtained, which makes it possible to effectively separate the silicon phase and the iron phase in the subsequent process. At the same time, by adjusting the holding time and cooling rate of each temperature zone, the iron-rich phase Al 3 FeSi 2 and Al 4 The content ratio of FeSi phase increases the iron-rich phase Al in the final solid phase. 3 FeSi 2 Due to the iron-rich phase Al 3FeSi 2 and Al 4 The morphology of FeSi grains is obviously different. 3 FeSi 2 phase is more likely to grow into coarse grains, while the Al 4 The FeSi phase tends to grow into fine needles. The needle-shaped grains are very easy to break into smaller particles during the subsequent separation of the silicon phase and the iron phase, resulting in the inability to separate the two phases through the density difference between the iron phase and the silicon phase, and the inability to effectively obtain high value-added elemental silicon products. 3 FeSi 2 When it is dominant, large-particle iron-rich phase and silicon phase can be obtained by regulation, and the density difference between the two phases can be utilized to effectively achieve phase separation.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] 1. It provides a new application path for low-grade silicon-aluminum materials, which not only solves the pollution problem of low-grade silicon-aluminum solid waste, but also realizes the high added value utilization of such materials and broadens the raw material sources of industrial silicon and high-purity silicon.
[0042] 2. During the cooling and crystallization process of the aluminum-silicon-iron melt, the silicon phase precipitates and grows at high temperature; as the temperature decreases, the iron phase begins to precipitate and interweaves with the silicon phase to form a unique skeleton structure; as the temperature continues to drop, the remaining aluminum-silicon alloy melt solidifies and exists in the skeleton gaps formed by the silicon phase and the iron phase to form a solid block;
[0043] 3. In the process of forming the interwoven framework of silicon phase and iron phase, the aluminum silicon iron melt is gradually cooled or kept warm by precisely controlling the cooling mechanism, so as to control the size, morphology, phase composition and element composition of the crystal morphology of silicon phase and iron phase and the internal organizational structure of the alloy;
[0044] 4. During the cooling process of the aluminum-silicon-ferrosilicon melt, the silicon phase first precipitates at high temperature. By controlling the cooling rate, insulation temperature and time, the silicon phase gradually grows to a suitable size, which is more conducive to subsequent separation and extraction;
[0045] 5. According to the ratio of aluminum, silicon and iron in the raw materials, select the appropriate temperature zone for heat preservation or gradient cooling, and match the appropriate heat preservation time and cooling speed to effectively control the phase composition of the iron phase. The precipitated iron phase can be Al 4 FeSi、Al 3 FeSi 2 、Al 2 Fe 5 Si 5 、Al 9 Fe 5 Si 5、Al 3 Fe 3 Si 2 One or more of the above; and by adjusting the cooling process, the particle size and growth morphology of the iron phase can be effectively regulated during the transformation of different crystal phases, providing favorable conditions for the subsequent separation of the silicon phase and the iron phase;
[0046] 6. After strict temperature reduction control, the iron phase can grow into large-sized grains, and effectively improve the previous needle-shaped growth orientation, making it possible to separate silicon and iron. Combined with the density difference between the silicon phase and the iron phase, polysilicon products and iron-rich phase products can be obtained by gravity separation methods such as cyclone troughs and shaking tables. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 Micrograph of the silicon phase and iron phase skeleton structure formed in Example 1.
[0048] Figure 2 The solids remaining after centrifugation obtained in Example 1 (left) and a partial enlarged photograph (right). DETAILED DESCRIPTION
[0049] The following is a detailed description of an embodiment of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0050] Example 1
[0051] The coal gangue and coal crushed to a particle size of less than 100 mesh are uniformly mixed in a mass ratio of 1:0.71 to form a mixed material, wherein the Al content in the coal gangue is 2 O 3 The mass fraction is 43.78%, SiO 2 The mass fraction is 50.15%, Fe 2 O 3 The mass fraction is 1.69%, and the Al content in coal is 2 O 3 The mass fraction is 46.01%, SiO 2 The mass fraction is 45.10%, Fe 2 O 3The mass fraction is 4.75%, and then 6% of the mass of sulfite pulp binder and 10% of water are added in turn for mixing. Then the mixed materials are made into pellets in a pelletizing machine with a pelletizing pressure of 100MPa. The prepared pellets are dried and dehydrated at 120°C to obtain dry lumps with a moisture content of no more than 1%. The dry lumps are then placed in an electric arc furnace for reduction reaction at a smelting temperature of 2200-2500°C. When the melt is cooled to 1400°C, it is cast in a mold and placed in a tunnel kiln for gradient temperature control, cooling to 1000°C at 10°C / min; keeping at 1000°C for 30min; cooling to 800°C at 1.5°C / min; cooling to 700°C at 10°C / min; keeping at 700°C for 30min; cooling to 600°C at 2°C / min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample, such as Figure 1 The above samples were directly loaded into the hanging basket, the centrifuge was started at 600°C, the super gravity coefficient was 200g, the separation time was 180min, the melt was separated by a porous filter plate, and the melt was cooled and solidified to obtain a cast aluminum-silicon alloy that met industrial standards, in which the Fe mass fraction was 0.87% and the Si mass fraction was 12.78%.
[0052] The solid sample remaining after centrifugation (such as Figure 2 As shown), the sample to be separated is crushed by a hammer crusher in a cyclic crushing mode, and 120-200 mesh samples are obtained by screening. The solid-liquid ratio of the crushed material is adjusted to 1:25, and the slurry is injected into the beneficiation shaker at a flow rate of 20ml / s. The inclination of the beneficiation shaker is set to 7°, and the flushing water flow of the beneficiation shaker is set to 50ml / s. A dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase to collect silicon-enriched phase samples. The collected high-silicon sample is then injected into the beneficiation shaker again at a flow rate of 10ml / s. The inclination of the beneficiation shaker is set to 5°, and the flushing water flow of the beneficiation shaker is set to 30ml / s. At this time, the dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase, 10mm away from the silicon phase. The high-silicon sample collected again has an iron content of 0.32%. After the high-silicon sample is soaked in 2mol / L hydrochloric acid for 24 hours, a small amount of impurities such as iron and residual aluminum are washed away to obtain a single-substance silicon product with a purity of 99.5%.
[0053] The above process can obtain 50.6 kg of cast silicon aluminum alloy and 21.5 kg of high-purity silicon product for every 100 kg of melt. The specific product conditions are shown in Table 1.
[0054] Example 2
[0055] The coal gangue and coal crushed to a particle size of less than 100 mesh are uniformly mixed in a mass ratio of 1:0.71 to form a mixed material, wherein the Al content in the coal gangue is 2 O 3The mass fraction is 42.96%, SiO 2 The mass fraction is 51.07%, Fe 2 O 3 The mass fraction is 1.54%, and the Al content in coal is 2 O 3 The mass fraction is 46.01%, SiO 2 The mass fraction is 45.10%, Fe 2 O 3 The mass fraction is 4.75%, and then 6% of the mass of the mixed material is added with sulfite pulp binder and 10% of water to mix the materials. Then the mixed materials are made into pellets in a pelletizing machine, and the pelletizing pressure is 100MPa. The prepared pellets are dried and dehydrated at 120℃ to obtain dry agglomerates, and the moisture content is required to be no more than 1%. Then the dry agglomerates are placed in an electric arc furnace for reduction reaction, and the smelting temperature is 2200-2500℃. When the melt is cooled to 1400℃, it is cast in a mold and placed in a tunnel kiln for gradient temperature control, cooling to 900℃ at 10℃ / min; keeping at 900℃ for 30min; cooling to 750℃ at 1℃ / min; cooling to 700℃ at 10℃ / min; keeping at 700℃ for 30min; cooling to 650℃ at 2℃ / min. At this time, a skeleton structure composed of large-scale silicon phases and coarse-grained iron phases has been formed inside the sample. The above samples were directly loaded into a hanging basket, placed in an ultragravity centrifuge equipped with a heating device, and the centrifuge was started at 650°C. The ultragravity coefficient was 200g, the separation time was 180min, and the melt was separated by a porous filter plate. After the melt was cooled and solidified, a cast aluminum-silicon alloy that met industrial standards was obtained, in which the Fe mass fraction was 0.89% and the Si mass fraction was 12.85%.
[0056] The solid materials left after centrifugation are first crushed into small pieces of 10-20mm using a hammer crusher, and then the samples are wet crushed using a disc crusher, and sieved with a wet vibrating screen to obtain samples of 120-200 mesh. The solid-liquid ratio of the crushed material is adjusted to 1:25, and the slurry is injected into the mineral processing shaker at a flow rate of 20ml / s. The inclination of the mineral processing shaker is set to 7°, and the flushing water flow of the mineral processing shaker is set to 50ml / s. A dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase to collect silicon-enriched phase samples. The collected high-silicon sample is then injected into the mineral processing shaker again at a flow rate of 10ml / s. The inclination of the mineral processing shaker is set to 5°, and the flushing water flow of the mineral processing shaker is set to 30ml / s. At this time, the dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase, 10mm away from the silicon phase. The high-silicon sample collected again has an iron content of 0.29%. After the high-silicon sample was soaked in 2mol / L hydrochloric acid for 24 hours, a small amount of impurities such as iron and residual aluminum were washed away to obtain a high-purity silicon product with a purity of 99.8%.
[0057] The above process can obtain 48.6kg of cast silicon-aluminum alloy and 23.5kg of high-purity silicon product for every 100kg of melt. The specific product conditions are shown in Table 1.
[0058] Example 3
[0059] The coal gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.75 to form a mixed material, wherein Al in the coal gangue component is 2 O 3 The mass fraction is 43.25%, SiO 2 The mass fraction is 47.56%, Fe 2 O 3 The mass fraction is 4.45%, and the Al content in coal is 2 O 3 The mass fraction is 46.01%, SiO 2 The mass fraction is 45.10%, Fe 2 O 3 The mass fraction is 4.75%, and then 6% of the mass of the mixed material is added with sulfite pulp binder and 10% of water to mix the materials. Then the mixed materials are made into pellets in a pelletizing machine with a pelletizing pressure of 100MPa. The prepared pellets are dried and dehydrated at 120℃ to obtain dry agglomerates with a moisture content of no more than 1%. Then the dry agglomerates are placed in an electric arc furnace for reduction reaction at a smelting temperature of 2200-2500℃. When the melt is cooled to 1400℃, it is cast in a mold and placed in a tunnel kiln for gradient temperature control, cooling to 950℃ at 10℃ / min; keeping at 950℃ for 30min; cooling to 850℃ at 1℃ / min; keeping at 850℃ for 30min; cooling to 600℃ at 2℃ / min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample. The above samples were directly loaded into a hanging basket, placed in an ultragravity centrifuge equipped with a heating device, and the centrifuge was started at 600°C. The ultragravity coefficient was 200g, the separation time was 180min, and the melt was separated by a porous filter plate. After the melt was cooled and solidified, a cast aluminum-silicon alloy that met industrial standards was obtained, in which the Fe mass fraction was 0.82% and the Si mass fraction was 11.96%.
[0060] The solid sample left after centrifugation is crushed by a hammer crusher in a cyclic crushing mode, and the sample to be separated is screened to obtain a sample of 120-200 mesh. The slurry is prepared into a slurry of about 10% by using a rotary chute for sorting. According to the color of the fan-shaped surface formed by the slurry falling in the selection chute, the scraper position is adjusted to collect the slurry with a smaller density (outer circle), which is a high-silicon sample with an iron content of 0.46%. After the high-silicon sample is soaked in 2mol / L hydrochloric acid for 24 hours, a small amount of impurities such as iron and residual aluminum are washed away to obtain a single-substance silicon product with a purity of 99.0%.
[0061] The above process can obtain 51.9kg of cast silicon-aluminum alloy and 22.3kg of high-purity silicon product for every 100kg of melt. The specific product conditions are shown in Table 1.
[0062] Example 4
[0063] The coal gangue and coal crushed to a particle size of less than 100 mesh are uniformly mixed in a mass ratio of 1:0.79 to form a mixed material, wherein the Al content in the coal gangue is 2 O 3 The mass fraction is 40.35%, SiO 2 The mass fraction is 45.89%, Fe 2 O 3 The mass fraction is 8.22%, and the Al content in coal is 2 O 3 The mass fraction is 46.01%, SiO 2 The mass fraction is 45.10%, Fe 2 O 3 The mass fraction is 4.75%, and then 6% of the mass of the mixed material is added with sulfite pulp binder and 10% of water to mix the materials. Then the mixed materials are made into pellets in a pelletizing machine with a pelletizing pressure of 100MPa. The prepared pellets are dried and dehydrated at 120℃ to obtain dry agglomerates with a moisture content of no more than 1%. Then the dry agglomerates are placed in an electric arc furnace for reduction reaction at a smelting temperature of 2200-2500℃. When the melt is cooled to 1400℃, it is cast in a mold and placed in a tunnel kiln for gradient temperature control. The gradient temperature control is carried out, and the temperature is reduced to 950℃ at 10℃ / min; 850℃ at 1℃ / min; 800℃ at 10℃ / min; 650℃ at 2℃ / min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample. The above samples were directly loaded into a hanging basket, placed in an ultragravity centrifuge equipped with a heating device, and the centrifuge was started at 650°C. The ultragravity coefficient was 200g, the separation time was 180min, and the melt was separated by a porous filter plate. After the melt was cooled and solidified, a cast aluminum-silicon alloy that met industrial standards was obtained, in which the Fe mass fraction was 1.45% and the Si mass fraction was 14.36%.
[0064] The remaining 76.87kg solid sample after centrifugation was crushed by a hammer crusher in a cyclic crushing mode, and the sample to be separated was screened to obtain a sample of 120-200 mesh. The solid-liquid ratio of the crushed material was adjusted to 1:25, and the slurry was injected into the mineral processing shaker at a flow rate of 20ml / s. The inclination of the mineral processing shaker was set to 7°, and the flushing water flow of the mineral processing shaker was set to 50ml / s. A dividing plate was set at the interface between the gray iron phase and the bright silver silicon phase to collect silicon-enriched phase samples. The collected high-silicon sample was then injected into the mineral processing shaker again at a flow rate of 10ml / s. The inclination of the mineral processing shaker was set to 5°, and the flushing water flow of the mineral processing shaker was set to 30ml / s. At this time, the dividing plate was set at the interface between the gray iron phase and the bright silver silicon phase, 10mm away from the silicon phase. The high-silicon sample collected again had an iron content of 0.36%. After the high-silicon sample was soaked in 2 mol / L hydrochloric acid for 24 hours, a small amount of impurities such as iron and residual aluminum were washed away to obtain a single-substance silicon product with a purity of 99.3%.
[0065] The above process can obtain 49.3kg of cast silicon aluminum alloy and 23.1kg of high-purity silicon product for every 100kg of melt. The specific product conditions are shown in Table 1.
[0066] Table 1
[0067]
[0068]
Claims
1. A method for producing high-purity silicon by comprehensive utilization of aluminum-silicon raw materials through precise gradient cooling and centrifugation, characterized in that: The steps are: (1) crushing the silicon-aluminum raw material and the carbonaceous reducing agent, adding a binder and water to mix them evenly, forming agglomerates, drying to obtain dry agglomerates, and then putting them into an electric arc furnace for reduction reaction to obtain a single-element aluminum-ferrosilicon melt; (2) Under controlled cooling conditions, the obtained aluminum-silicon-iron melt is subjected to gradient cooling, wherein the gradient cooling includes the following stages: in the first stage, the temperature is reduced to 800-1300° C. at a cooling rate of 1-20° C. / min and kept at this temperature for 10-200 min; in the second stage, the temperature is reduced to 650-1000° C. at a cooling rate of 0.1-20° C. / min and kept at this temperature for 10-200 min; in the third stage, the temperature is reduced to 600-850° C. at a cooling rate of 0.1-20° C. / min and kept at this temperature for 10-200 min; in the fourth stage, the temperature is reduced to 577-650° C. at a cooling rate of 0.1-20° C. / min to obtain a silicon-aluminum-iron alloy with a skeleton structure; (3) the obtained silicon-aluminum-iron alloy with a skeleton structure is heated to 577-700° C. and centrifuged to achieve solid-liquid separation, wherein the solid state is an interwoven skeleton structure formed by the growth of silicon phase and iron phase; (4) crushing and sieving the solid porous interwoven skeleton structure sample composed of silicon phase and iron phase skeleton obtained in the previous step to 40-200 mesh; (5) The sieved sample obtained in the previous step is subjected to gravity separation to separate the silicon phase and the iron phase, and the low-density sample is collected as a high-silicon sample; (6) The high-silicon sample obtained in the previous step is soaked in 1-5 mol / L hydrochloric acid for 24 hours to obtain elemental silicon with a purity higher than 99.9%, i.e., the high-purity silicon.
2. The method according to claim 1, characterized in that: The silicoalumina raw material is a low-grade silicoalumina raw material, in which the Al2O3 content is not higher than 55%, and the Al / Si ratio is not higher than 3.
3. The method according to claim 1, characterized in that The silicon-alumina raw material in step (1) is one or a mixture of natural silicon-alumina minerals, solid waste containing silicon-alumina, or artificially synthesized silicon-alumina raw materials, wherein the natural silicon-alumina minerals include bauxite, kaolinite, albite, and potassium feldspar, and the solid waste containing silicon-alumina includes bauxite flotation tailings, coal gangue, fly ash, and shale slag.
4. The method according to claim 1, characterized in that: After the silicon-aluminum raw material and the carbonaceous reducing agent in step (1) are added together, the ratio of aluminum, silicon and iron is as follows: the aluminum content is 10-88.3wt.%, the silicon content is 11.7-90wt.%, the iron content is 0.01-26.0wt.%, and the iron content is ≤(45.64-0.52Al)wt.% and ≤(40.63-0.41Si)wt.%.
5. The method according to claim 1, characterized in that In the above method, the amount of the carbonaceous reducing agent in step (1) is 90-95% of the required reducing agent amount.
6. The method according to claim 1, characterized in that Step (3) centrifuges the silicon-aluminum-iron alloy with a skeleton structure, keeps warm for 0 to 360 minutes, has a supergravity coefficient of 50 to 500 g, and a separation time of 30 to 360 minutes.
7. The method according to claim 1, characterized in that The gravity separation described in step (5) is carried out by using a shaking table for separation. The sample after crushing in step (4) is adjusted to a solid-liquid ratio of 1:10 to 1:50, and the slurry is injected into the ore dressing shaking table at a flow rate of 10 to 30 ml / s. The inclination angle of the ore dressing shaking table is set to 5-10°, and the flushing water flow of the ore dressing shaking table is set to 20 to 100 ml / s. A dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase to collect silicon-rich phase samples, i.e., high-silicon samples; the collected high-silicon samples are injected into the ore dressing shaking table again at a flow rate of 5 to 20 ml / s, the inclination angle of the ore dressing shaking table is set to 3 to 6°, and the flushing water flow of the ore dressing shaking table is set to 20 to 40 ml / s. At this time, the dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase, 5 to 15 mm away from the silicon phase, and the high-silicon samples are collected again.
8. The method according to claim 1, characterized in that: The gravity separation described in step (5) is carried out by using a cyclone chute to prepare a slurry of about 2-40% of the crushed sample in step (4). After separation, the collected samples with low density are polycrystalline silicon, and the samples with high density are iron-rich phase.
9. The method according to claim 1, characterized in that: The gravity separation described in step (5) adopts a two-product heavy medium cyclone for separation. The solid-liquid ratio of the sample to the heavy medium suspension after screening is 1:2.5-1:4.5, the volume concentration of the heavy medium suspension is 15%-30%, and the heavy medium suspension is composed of one or more of sodium polytungstate, calcium bromide, zinc bromide or calcium iodide. After sorting, the collected low-density sample is polycrystalline silicon; the high-density sample is an iron-rich phase.
10. The method according to claim 1, characterized in that The pickling solution in step (6) can be one or more of hydrochloric acid, nitric acid or sulfuric acid, or can be one or more of hydrofluoric acid and hydrochloric acid, nitric acid and sulfuric acid, wherein the concentration of hydrofluoric acid is 0% to 5%, the concentration of the mixed acid solution is 5% to 20%, the solid-liquid ratio is 1:1 to 1:5, the pickling temperature is room temperature to 90°C, the pickling time is 1 to 12h, and the stirring speed is 0 to 300rpm.
Citation Information
Patent Citations
Method for preparing aluminum-silicon-iron alloy from high-aluminum coal gangue and conducting graded purification
CN113913621A
A method for preparing aluminum-silicon-iron alloy using high-aluminum fly ash and grading purification
CN114480855B